Serum IL-18 as biomarker in predicting long-term renal outcome among pediatric-onset systemic lupus erythematosus patients. Issue 40 (October 2016) - Wu, Chao-Yi; Yang, Huang-Yu; Yao, Tsung-Chieh; Liu, Su-Hsun; Huang, Jing-Long
Abstract : Abstract: An urge of biomarker identification is needed to better monitor lupus nephritis (LN) disease activity, guide clinical treatment, and predict patient's long-term outcome. With the proinflammatory effect and its association with inflammasomes, the significance of interleukin-18 (IL-18) among pediatric-onset systemic lupus erythematous (pSLE) patient, especially, its importance in predicting long-term renal outcome was investigated. In a pSLE cohort of 96 patients with an average follow-up period of 10.39 ± 3.31 years, clinical data and laboratory workups including serum IL-18 were collected at time of disease onset and 6 months after treatment despite their initial renal status. Through Cox regression analysis, the parameters at baseline and at 6 months posttreatment were carefully analyzed. Average age of all cases was 12.74 ± 3.01 years old and 65 of them underwent renal biopsy at the time of diagnosis. Nine subjects (9.38%) progressed to end-stage renal disease (ESRD) and 2 cases (2.08%) died during follow-up. Through multivariate analysis, serum IL-18 level 6 months posttreatment was found to be the most unfavorable factor associating poor clinical outcome despite patient's initial renal status. In addition, the presentation of serum IL-18 in its correlation with SLE global disease activity as well as the presence and severity of LN were all significant ( P < 0.001, P = 0.03, and P = 0.02, respectively). The histological classification of LN, however, was not associated with the level of IL-18 among the pSLE patients ( P = 0.64). The role of serum IL-18 as biomarker representing global disease activity and status of renal flares among pSLE population was shown for the first time. Additionally, we have identified IL-18 at 6 months posttreatment a novel marker for long-term renal outcome prediction.